GREEN SYNTHESIS, CHARACTERIZATION, PHOTOCATALYTIC ACTIVITY OF ZnO/TiO2 NANOCOMPOSITE FROM Carica papaya LEAVES - Safira Salsabilla; Dina Kartika Maharani (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2023)
This study aims to synthesize a ZnO/TiO2 (ZT) nanocomposite from Carica papaya leaf extract and evaluate its photocatalytic activity. The ZT nanocomposite was prepared using the sol-gel method with ZnO/TiO2 4-gram (ZT4) concentration variations and ZnO/TiO2 6-gram (ZT6). Methylene Blue (MB) was used as a model dye to test its photocatalytic properties. The trend for most activity is shown by ZT4 UV light 40 mg and ZT6 UV light (60 mg), which is 87%. Characterization of ZnO/TiO2 (ZT) nanocomposite using FTIR and XRD The ZT4 nanocomposite had an average crystallite size of approximately 12 nm and crystallinity percentage of 92%, whereas the ZT6 nanocomposite had an average crystallite size of approximately 6 nm and crystallinity percentage of 97%. FTIR resulted in some group C=C stretching alkene, C-H stretching vibrations of an aromatic aldehyde, and O-H stretching of alcohols and Zn-Ti-O in the fingerprint region 393.48 cm-1 to 987.55 cm-1 for ZT4 and in the fingerprint region 401.19 cm-1 to 864.11 cm-1 for ZT6.